IMPLEMENTASI MODEL PENILAIAN HOTS (HIGHER ORDER THINKING SKILLS) DALAM MAHARAH KALAM PADA MAHASISWA PENDIDIKAN DOKTER UIN MAULANA MALIK IBRAHIM MALANG - Toifah, Nur (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Maharah kalam is one of the four maharat in Arabic, which is important to learn so that students can communicate orally properly and correctly so that the delivery of the message can be received. Meanwhile, the HOTS (Higher Order Thinking Skill) assessment in maharah kalam is an assessment that includes three cognitive domains of analyzing, assessing/evaluating, and creating/creating, which is combined with the domain of 21st-century skills. This study examines the implementation of HOTS assessment in maharah kalam in the Study Program of Medical Education UIN Malang. While this type of research is descriptive qualitative research, and the data collection uses triangulation techniques, namely observation, documentation, and literacy. The data that has been collected is reviewed or analyzed, classified, reduced, and then described. The result of this study is that the HOTS (Higher Order Thinking Skills) assessment on maharah kalam must be implemented by aligning the form of assessment and the dimensions of the HOTS thinking process, namely analyzing (C4) 10%, evaluating (C5) 15%, and creating (C6) 75%. With this assessment, students are expected to be able to implement 21st-century skills that include critical thinking skills, problem-solving skills, communication skills, collaboration, information literacy, media, and technology that can make them able to be creative, collaborative, and innovative. While the assessment component include understanding 25%, grammar 20%, vocabulary 20%, fluency 15%, and fluency of speech 20%.